let L be non empty LattStr ; :: thesis: ( L is meet-idempotent & L is join-idempotent & L is meet-commutative & L is join-commutative & L is meet-associative & L is join-associative & L is satisfying_QLT1 & L is satisfying_QLT2 & L is modular implies for v1, v2, v3 being Element of L holds (v1 "/\" v2) "\/" (v1 "/\" v3) = v1 "/\" (v2 "\/" (v1 "/\" v3)) )

assume A0: ( L is meet-idempotent & L is join-idempotent & L is meet-commutative & L is join-commutative & L is meet-associative & L is join-associative & L is satisfying_QLT1 & L is satisfying_QLT2 & L is modular ) ; :: thesis: for v1, v2, v3 being Element of L holds (v1 "/\" v2) "\/" (v1 "/\" v3) = v1 "/\" (v2 "\/" (v1 "/\" v3))

then A1: ( ( for v0 being Element of L holds v0 "/\" v0 = v0 ) & ( for v2, v1, v0 being Element of L holds (v0 "/\" v1) "/\" v2 = v0 "/\" (v1 "/\" v2) ) & ( for v1, v0 being Element of L holds v0 "/\" v1 = v1 "/\" v0 ) & ( for v0, v2, v1 being Element of L holds (v0 "/\" (v1 "\/" v2)) "\/" (v0 "/\" v1) = v0 "/\" (v1 "\/" v2) ) & ( for v0 being Element of L holds v0 "\/" v0 = v0 ) & ( for v2, v1, v0 being Element of L holds (v0 "\/" v1) "\/" v2 = v0 "\/" (v1 "\/" v2) ) & ( for v1, v0 being Element of L holds v0 "\/" v1 = v1 "\/" v0 ) & ( for v0, v2, v1 being Element of L holds (v0 "\/" (v1 "/\" v2)) "/\" (v0 "\/" v1) = v0 "\/" (v1 "/\" v2) ) ) by LATTICES:def 4, LATTICES:def 5, LATTICES:def 6, LATTICES:def 7, SHEFFER1:def 9, ROBBINS1:def 7;

for v0, v1, v2 being Element of L st v0 "\/" v1 = v1 holds

v0 "\/" (v2 "/\" v1) = (v0 "\/" v2) "/\" v1 by A0, LATTICES:def 3, LATTICES:def 12;

hence for v1, v2, v3 being Element of L holds (v1 "/\" v2) "\/" (v1 "/\" v3) = v1 "/\" (v2 "\/" (v1 "/\" v3)) by QLTMod, A1; :: thesis: verum

assume A0: ( L is meet-idempotent & L is join-idempotent & L is meet-commutative & L is join-commutative & L is meet-associative & L is join-associative & L is satisfying_QLT1 & L is satisfying_QLT2 & L is modular ) ; :: thesis: for v1, v2, v3 being Element of L holds (v1 "/\" v2) "\/" (v1 "/\" v3) = v1 "/\" (v2 "\/" (v1 "/\" v3))

then A1: ( ( for v0 being Element of L holds v0 "/\" v0 = v0 ) & ( for v2, v1, v0 being Element of L holds (v0 "/\" v1) "/\" v2 = v0 "/\" (v1 "/\" v2) ) & ( for v1, v0 being Element of L holds v0 "/\" v1 = v1 "/\" v0 ) & ( for v0, v2, v1 being Element of L holds (v0 "/\" (v1 "\/" v2)) "\/" (v0 "/\" v1) = v0 "/\" (v1 "\/" v2) ) & ( for v0 being Element of L holds v0 "\/" v0 = v0 ) & ( for v2, v1, v0 being Element of L holds (v0 "\/" v1) "\/" v2 = v0 "\/" (v1 "\/" v2) ) & ( for v1, v0 being Element of L holds v0 "\/" v1 = v1 "\/" v0 ) & ( for v0, v2, v1 being Element of L holds (v0 "\/" (v1 "/\" v2)) "/\" (v0 "\/" v1) = v0 "\/" (v1 "/\" v2) ) ) by LATTICES:def 4, LATTICES:def 5, LATTICES:def 6, LATTICES:def 7, SHEFFER1:def 9, ROBBINS1:def 7;

for v0, v1, v2 being Element of L st v0 "\/" v1 = v1 holds

v0 "\/" (v2 "/\" v1) = (v0 "\/" v2) "/\" v1 by A0, LATTICES:def 3, LATTICES:def 12;

hence for v1, v2, v3 being Element of L holds (v1 "/\" v2) "\/" (v1 "/\" v3) = v1 "/\" (v2 "\/" (v1 "/\" v3)) by QLTMod, A1; :: thesis: verum